Confocal Raman spectroscopy: In vivo measurement of physiological skin parameters – A pilot study - Binder, Lisa; SheikhRezaei, Safoura; Baierl, Andreas; Gruber, Lukas; Wolzt, Michael; Valenta, Claudia (Journal of dermatological science, 2017)
•Depth concentration profiles for skin parameters were generated in vivo by CRS.•The curve profiles of in vivo data could be visualised within a few minutes.•The correlation between skin and blood cholesterol levels was investigated. In vivo application of confocal Raman spectroscopy (CRS) allows non-invasive depth measurement of the skin. Thereby obtained knowledge of the skin composition is essential to reliably assess the actual skin state. Besides other components, the skin cholesterol concentration is of interest; however, little is known about its connection to the cholesterol concentration quantified in venous blood. In this study, the skin composition of the volar forearm was characterised in vivo using CRS. In particular, the potential of CRS as a non-invasive method to determine cholesterol levels was validated. Raman spectra of the volar forearm of 15 participants were recorded twice within two weeks. Depth concentration profiles for major skin components were generated. Stratum corneum (SC) thickness was calculated from water concentration profiles. In order to examine the usability of dermal CRS for cholesterol level determination, results were compared to fasting total cholesterol values in venous blood as determined by an enzymatic method. Depth concentration profiles for the skin components of interest showed a comparable curve progression for the participants. It was possible to link changes in concentration to physiological processes. Moreover, age-related differences could be found. Several novel mathematical approaches for the comparison of the skin cholesterol content and the blood cholesterol concentration have been developed. However, no correlation passed the Bonferroni multiple testing correction. CRS serves as useful tool for the in vivo monitoring of skin components and hydration. Concentration depth profiles provide information about the current skin condition. No distinct correlation between the skin and blood cholesterol concentration was found within the scope of the present study. Concerning this matter, the heterogeneous distribution of cholesterol in the skin may be a factor influencing these results.